Ships and Shipwrecks Stories from the Great Lakes. - Gebhart, Richard (Greenstone Bks., 2021)
"In this book, Richard Gebhart tells the tales of Great Lakes ships and their captains and crews, from their launches to their sad demises-or sometimes, their celebrated retirements"--